USING AUTHENTIC MATERIALS AND TASKS TO DEVELOP CRITICAL THINKING AND ANALYTICAL SKILLS IN ENGLISH LESSONS (Web of Teachers: Inderscience Research, 2024)
In this article, we will look at how to effectively develop critical thinking in students in English lessons using authentic materials and specially designed tasks. The article aims to provide English teachers with practical recommendations and strategies that will help them develop students' critical thinking skills, which are essential for a successful life and career in modern society.